N. V. MASLIUK: SEMANTIC-SYNTACTIC FUNCTIONS OF SYNCRETIC SUBORDINATE-COORDINATE CONJUNCTIONS (ON THE MATERIAL OF V. SHEVCHUK’S NOVELS) - MASLIUK, N. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
antic specificity of simple and composite sentences with an eye to the peculiarities of the use of connecting means. The corpus of illustrative material is actively supplemented by examples from fiction discourse, which create a basis for studying syncretic functioning of connecting means. Purpose of this article is to find out the specificity of semantic-syntactic function of subordinate-coordinate conjunctions in the Valeriy Shevchuk’s novels. Methods. In order to achieve the purpose the following methods were used: linguistic description of lingual facts, context analysis, quantitative calculations. Results. The approach to the classification of connecting means used in the work made it possible to characterize the semantic-syntactic potential of syncretic subordinate-coordinate conjunctions in fiction discourse in the projection of Valeriy Shevchuk’s idiostyle. The specificity of the four main groups of connecting means: disjunctive-explanatory, disjunctive-concessive, partitive-concessive, of comparison and correspondence is analyzed. The activity of functioning and peculiarities of semantic-syntactic demonstration of each group is confirmed by examples from the works of the writer. Among the most active of the disjunctive-explanatory conjunctions are тобто, чи; within disjunctive-concessive group – але, однак, проте; the partitive-concessive group – хоч … хоч, чи то …чи то. The conjunctions of comparison and correspondence are not represented in the analyzed works of the writer. Each semantic-syntactic group of conjunctions is correlated with the corresponding type of composite sentence or with a syntactic variant of a simple complicated sentence. The quantitative indicators of the frequency of each conjunction’s occurrence are determined. Originality. The originality of the scientific research lies in the complex analysis of the specificity of semantic-syntactic function of subordinate-coordinate conjunctions in the Valeriy Shevchuk’s novels «Three Leaves by the Window», «The House on the Mountain», «On the Humbled Field», «The Eye of the Abyss». Conclusion. It concludes that the peculiarities of subordinate-coordinate conjunctions in the Valeriy Shevchuk’s works correspond to the new classification of conjunctions by K. Gorodenska and represent the semantic-syntactic relations differentiated by the researcher. The quantitative demonstration of the subordinate-coordinate conjunctions in the creative elaboration of the writer is determined. The most productive are the following conjunctions: але (59 %), тобто (20,9 %), чи (11,5 %). The use of conjunctions alone (однак (4,7 %), чи…чи (4,1 %), проте (2,0 %), хоч…хоч (1,5 %) is less frequent. The least used are себто, зате, та, чи то…чи то (0,5 % each). The writer gives preference to syncretic composite sentence, subordinate-coordinate in form and content, the means of connection in which are syncretic disjunctive-concessive conjunctions. This explains the highest frequency of use of the conjunction але. The syncretism of the use of the coordinate conjunctions in sentences of the type that has not been classified before, especially the one with subordinate and asyndetical relations, is determined. The prospect of further scientific researches lies in the investigation of the semantic-syntactic sphere of functioning of other kinds of syncretic connecting means in the projection on the individual style of the writer.